Conceptual and category apparatus of legislation, what determines legal responsibility in pharmaceutical activity - O. H. Aleksieiev (Zaporozhye State Medical University, 2022)
The aim of the work - is to study the conceptual and categorical apparatus of the legislation of Ukraine, which determines the legal responsibility in pharmaceutical activities. Materials and methods. The study is based on a number of legislative terms and case law in cases of prosecuting violators of pharmaceutical legislation. During the work, we used methods of information retrieval, analysis, systematization, and generalization. Results. It is established that pharmaceutical activity is one of the branches in the field of health care, which is carried out by conducting licensed economic activities by economic entities and professional activities by non-economic entities - pharmaceutical workers. The complex nature of such activities determines the establishment by the state at the legislative level of various types of legal liability: criminal, administrative, civil, and disciplinary. Conclusions. Legal responsibility in pharmaceutical activity is characterized by a certain terminological inconsistency and unsystematic nature, which is manifested in the lack of disclosure of the meanings of such terms as pharmaceutical activity (its types and directions), pharmaceutical care, pharmaceutical service; subject of pharmaceutical activity (with the separation of categories of persons with appropriate legal status). The conceptual and categorical apparatus of legislation governing pharmaceutical activities needs urgent unification, as the imbalance of legislative terminology results in inadequacy and inconsistency both in the conceptual sense of the institution of legal responsibility and in bringing participants of pharmaceutical activity to legal responsibility for relevant offenses.